Rok Miłosza w czasopismach literackich - Kałowska, Agnieszka (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The article is a review of important articles concerning the works of Czesław Milosz which were published in 2011, the Year of Czeslaw Milosz. The author investigates which aspects of the poet’s works are still interesting for researchers and whether any new interpretive perspectives have emerged.